Analisis Faktor-Faktor Yang Mempengaruhi Pengungkapan Corporate Social Responsibility Pada Perusahaan Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia - Ryan Anggie; Anis Rachma Utary; Muhammad Subhan (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
The purpose of this research is to see the effects of Institutional Ownership, Managerial Ownership, Profitability, Leverage, and Company Size, over Corporate Social Responsibility’s Disclosure. And for knowing, do the companies listed on the Indonesia Stock Exchange, Period 2013-2015 on Basic Industry and Chemicals Sector have been implementing Corporate Social Responsibility Disclosure optimally. The method used in this research was purposive sampling. The data used’re secondary sourced, obtained from the annual reports of 36 companies with 108 total samples. The analyzing technique used is multiple linear regression analyzed by the 24th version of SPSS program. Item disclosure is divided into six categories, Environment, Energy, Health and Safety Training, Products, Community involvement, and General. The total number of items from each category are 78 items, based on CSR Index used with Wondabio dan Sayekti (2007). The results obtained are, Institusional Ownership, Managerial Ownership and Company Size are positive and have significantly impact, the Disclosure of Corporate Social Responsibility. Profitability, and Leverage are negatif, only Leverage has a possitive impact over the Disclosure of Corporate Social Responsibility.Keywords: Corporate Social Responsibility Disclosure, Stakeholder, Shareholders, Financial Ratio.